不同喷砂条件对选择性激光熔覆钴铬合金金瓷结合强度影响的研究 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2018)
OBJECTIVE: To investigate the effect of different sandblasting conditions on the metal-ceramic bonding strength of Co-Cr alloy fabricated by selective laser melting (SLM) technology. METHODS: A total of 63 specimens of Co-Cr alloy fabricated by SLM were prepared and randomly divided into nine groups (n=7). Each group was treated with different powder particles (A1=50 µm, A2=100 µm, and A3=150 µm) and pressures (B1=0.2 MPa, B2=0.4 MPa, and B3=0.6 MPa) in sandblasting. One sample was randomly selected from each group for microstructure observation by scanning electron microscope (SEM). Ceramic was fired at the center of the specimens. Metal-ceramic bonding strength was measured with universal testing machine. Results were statistically analyzed with SPSS 17.0 software. RESULTS: The mean bond strengths were as follows: Group A1B1: 27.22 MPa±0.95 MPa, Group A1B2: 27.58 MPa±0.47 MPa, Group A1B3: 26.80 MPa±0.71 MPa, Group A2B1: 27.54 MPa±0.78 MPa, Group A2B2: 30.75 MPa±0.43 MPa, Group A2B3: 26.93 MPa±0.88 MPa, Group A3B1: 28.18 MPa±0.93 MPa, Group A3B2: 29.55 MPa±0.57 MPa, and Group A3B3: 28.11 MPa±0.91 MPa. The particle factor of Al(2)O(3) and the pressure factor of blasting showed statistical significance (P<0.05). An interaction was observed between the factors of particle and pressure (P<0.05). Mixed fracture mode of all specimens was observed after the shear strength test. CONCLUSION: In conclusion, metal-ceramic bonding strength reaches the maximum when specimens are sandblasted with 100 µm alumina oxide at 0.4 MPa pressure.